Reservoir quality controls and reservoir modelling of continental to transitional shallow marine sedimentary basins of Southern Nigeria - Adamolekun, Olajide Jonathan (KIT Scientific Publishing, 2023)
The object-based stochastic approach in facies modelling is important in the construction of geologically consistent 3-D reservoir models and in constraining the distribution of petrophysical properties. Tortuosity factor, facies, porosity and cementation factor constitute major uncertainties in the generated 3-D static model of the Niger Delta Basin. Reservoir quality in the Dahomey Basin is mainly controlled by detrital matrix, carbonate cement, and iron oxide and iron oxyhydroxide cements.